Penerapan Metode Substruktur Dalam Analisis Dinamika Rotor - Ramses Hutahaean (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2014)
To analyze complex and large structures, there are difficulties on analizing the whole complete structure regarding the limited computer memories, a large degree of freedom requires a long execution time. In practical term, the analysis of the overall structure is also not efficient. If there is any changes to one component of the structure, it must be re-analyzed as a whole complete structure. By using substructure analysis, the analysis of complex and large structure become more efficient and pratical. In this paper will be disscussed the application of substructure analysis of disc-bladed rotor.